Decision Support System for Selecting the Best Rental House with Weight Product in Sidokare District, Sidoarjo Regency - Akas Bagus Setiawan; Eka Yuniar; Mujiono Mujiono; David Juli Ariyadi; Mas'ud Hermansyah (G-Tech: Jurnal Teknologi Terapan, 2026)
The demand for rental housing in high-mobility areas such as Sidokare District, Sidoarjo Regency, continues to increase along with the region's economic development. However, prospective tenants often face difficulties in selecting the right rental house due to unstructured information and subjective decision-making processes. This study aims to develop a web-based Decision Support System (DSS) capable of providing objective and measurable rental housing recommendations. The method used is the Weighted Product (WP), a multicriteria decision-making technique that normalizes weights through multiplication operations. This system evaluates five rental housing alternatives based on eight main criteria, including price, location, facilities, security, and comfort. The results show that Sukun Rental House is the best alternative with the highest preference value of 0.0769. The practical implication of this study is the availability of an efficient digital tool for residents and students in Sidokare to compare various housing options transparently and quickly. This system successfully minimizes subjectivity in housing selection and helps users find the housing that best suits their financial priorities and functional needs.